Interhospital Spread of blaVIM-1- and blaCTX-M-15-Producing K. pneumoniae ST15 on an IncR Plasmid in Southern Spain - Patricia Pérez-Palacios; Ana Gual-; Ines Portillo-Calderón; Esther Recacha-Villamor; Francisco Franco-Álvarez de Luna; Lorena Lopez-Cerero; Alvaro Pascual (MDPI AG, 2023)
In 2014-2015, the main CTX-M-15- and OXA-48-producing clone in our region was ST15. Recently, K. pneumoniae ST15 isolates co-producing VIM-1 and CTX-M-15 were detected in several hospitals. The aim was to study the emergence and acquisition of this carbapenemase. Between 2017 and 2019, four hospitals submitted twenty-nine VIM-1- and CTX-M-15-producing K. pneumoniae ST15 isolates to our laboratory. Seven representatives of each XbaI PFGE pulsotype were sequenced using short- and long-read technologies. RAST, CGE databases, and Pathogenwatch were used for resistance determinants and capsule-type analysis. Plasmid comparison was performed with Easyfig2.1. Phylogenetic analysis included other contemporary ST15 isolates from Spain. The 29 isolates were clustered into seven different pulsotypes. The selected genomes, from three hospitals in two different provinces, were clustered together (fewer than 35 alleles) and differed by more than 100 alleles from other ST15 isolates obtained in the region. These seven isolates harbored one IncR plasmid (200-220 kb) with a common backbone and four regions flanked by IS26: one contained blaVIM-1, another contained blaCTX-M-15, the third contained blaOXA-1, and the fourth harbored heavy-metal-tolerance genes. The two initial plasmids, from two different centers, were identical, and rearrangement of four regions was observed in the five subsequent plasmids. Our findings showed the first intercenter dissemination of IncR plasmids carrying blaVIM-1, blaCTX-M-15, and metal-tolerance genes mediated by a new lineage of K. pneumoniae ST15. Two different capture events of the blaVIM-1 gene or different IS26-mediated plasmid rearrangements from a common ancestor may explain plasmid variations.